PULMONARY ASPERGILLOSIS IN A GREAT DANE PUP: DIAGNOSIS AND MANAGEMENT - Abid Ali Bhat; M. Sandhya Bhavani; S. Kavita; B. Nagarajan; A. P. Nambi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present investigation screened a case with clinical signs of chronic cough, wheezing, weight loss and respiratory distress. The dog was subjected to physical examination, followed by radiographic and bronchoscopic evaluation. Radiographic examination of the thoracic cavity revealed increase in radiolucency of the entire alveolar soft tissue. Multiple bronchoalveolar lavages were collected; cytology, bacterial and fungal cultures were performed. No bacterial growth was detected upto 48 hours of incubation whereas cell cytology and fungal culture confirmed the diagnosis of Pulmonary Aspergillosis. The dog was treated with iatraconazole with no remission of clinical signs upto six months post treatment.